The prevalence and pattern of cannabis use among patients attending a methadone treatment clinic in Nairobi, Kenya - Elizabeth Wambui Ngarachu; Sarah Kanana Kiburi; Frederick R. Owiti; Rachel Kangethe (BMC, 2022)
Abstract Background Cannabis use during methadone treatment may negatively impact treatment outcomes. The aim of this study was to determine the prevalence and pattern of cannabis use among patients attending a methadone treatment clinic in Nairobi, Kenya. Methods This was a retrospective study of 874 patients on methadone therapy at a methadone maintenance treatment clinic in Nairobi, Kenya from December 2014 to November 2018. Data on sociodemographic characteristics and drug use patterns based on urine drug screens was collected from patient files. Data was analyzed using Statistical Package for the Social Sciences (SPSS) for windows version 23.0. Results Point prevalence of cannabis use was 85.8% (95% CI, 83.3 - 88.0) at baseline and 62.7% (95% CI, 59.5 - 65.8) during follow-up. A pattern of polysubstance use was observed where opioids, cannabis and benzodiazepines were the most commonly used drugs. The mean age of the patients was 35.3 (SD 9.0) years with the majority being male, unemployed (76%), (51.4%) had reached primary level of education, and (48.5%) were divorced or separated. University education was associated with reduced risk for cannabis use OR = 0.1 (95% CI, 0.02-0.8, p = 0.031). Conclusion Cannabis use is prevalent among patients attending a methadone treatment clinic in Kenya, suggesting need for targeted interventions to address the problem of cannabis use during methadone treatment.